Functional relationship between myology and ecology in carnivores: do forelimb muscles reflect adaptations to prehension?. (27th April 2019) - Böhmer, Christine; Fabre, Anne-Claire; Taverne, Maxime; Herbin, Marc; Peigné, Stéphane; Herrel, Anthony
Abstract: Prehension involves the ability to reach, grasp and transport an object. It is a fitness-relevant behaviour with an important role in food acquisition and locomotion. Grasping an item requires the coordinated action of several muscles and, consequently, the muscular anatomy can be expected to be a good indicator of grasping ability. Here, we quantitatively analyse the myology of the forelimb in Carnivora in relation to their grasping ability, arboreality and locomotor specializations. Carnivorans are a monophyletic group and a good model due to the fact that they vary in ecology and prehensile capabilities. We find that non-prehensile taxa differ in their muscle properties from poorly prehensile taxa and from intermediately to strongly prehensile taxa when taking into account variation in body size and phylogeny. Species with strong prehensile capabilities are characterized by a high force-producing capacity in the forelimb rotators. A strong grasp is not only advantageous for prehension, but also for climbing. Species with poor prehensile capabilities but an intermediate to high degree of arboreality display well-developed flexor muscles contributing to a strong grasp. Although anatomical adaptations for prehensility and arboreality are similar, the present study revealed differences in the muscle specializations of the forelimb in Carnivora.